إستراتيجية تدريس قواعد اللغة العربية بكتاب ألفية ابن مالك بالمدرسة الدينية الوسطى المؤيد سوراكرتا - Isnaini, Rohmatun Lukluk (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Arabic has a special place among the other languages of the world because Arabic is the language of the Qur'an and the Sunnah of Rasulullah SAW. To learn it, ulama agreed to put sharf and nahwu (qawaid) as the basis. One book that discusses is Alfiyah which is the book of Imam Jamaluddin Muhammad bin Abdullah bin Malik. In presenting qawaid in that kitab, the teacher requires special methods and strategies. For that by using descriptive qualitative research method, this research illustrates that a teacher at Madrasah Diniyah Wustha Al-Muayyad Surakarta using three methods, 1) qawaid wa tarjamah method, 2) Tahfidh wa Tasmi' method, and 3) lecturing method. Then, within each of these methods are translated into several strategies. The implementation of this strategy tailored to the Madrasah Diniyah Wustha at the environment Al-Muayyad boarding school in Surakarta.